Nursing educators' experiences regarding students' mistakes in clinical settings - Alehe Seyedrasooli; Vahid Zamanzadeh; Akram Ghahramanian; Faranak Jabbarzadeh Tabrizi (Wolters Kluwer Medknow Publications, 2019)
Background: There is always the possibility of mistakes for nursing students, given the nature of the clinical wards. Nursing educators are the primary figures responsible for the nursing students' performance in clinical wards. The present study intended to describe nursing educators' experiences in relation to clinical mistakes made by nursing students. Materials and Methods: The present research was conducted using a descriptive phenomenological approach in 14 nursing educators. Deep semistructured interviews were performed to gather data, and triangulation and member checking were utilized to ensure data integrity. The data were analyzed using Colaizzite seven-stage method. Results: The themes extracted through comparison and analysis included three main themes "encountering an unpleasant event", "internal confrontation" and "the change in the effectiveness of teaching" besides 6 sub-themes including "emotional excitement", "honest reaction to the issue", "struggling with the fear of recurrence of the mistake" "coping with the event", "passive teaching" and "trying to be enhance one's capabilities in teaching"Conclusions: Regardless of the possibility of gaining fruitful experiences from a clinical mistake, its occurrence could be followed by negative experiences and consequences for the educators. It is thus essential that appropriate packages in this regard be provided in the empowerment programs for young educators to prepare them for correct confrontation with mistake occurrence. It is suggested that further qualitative studies be conducted to extract the steps educators take in confrontation with nursing students' clinical mistakes.